2020
DOI: 10.1155/2020/9749631
|View full text |Cite
|
Sign up to set email alerts
|

Solanine Inhibits Immune Escape Mediated by Hepatoma Treg Cells via the TGFβ/Smad Signaling Pathway

Abstract: Objective. To observe the inhibitory effect of solanine on regulatory T cells (Treg) in transplanted hepatoma mice and to study the mechanism of solanine inhibiting tumor growth. Methods. The levels of Treg cells and IL-2, IL-10, and TGFβ in the blood of patients with liver cancer were detected by flow cytometry and ELISA, respectively. A mouse hepatocellular carcinoma (HCC) graft model was established and randomly divided into four groups: control group, solanine group, TGFβ inhibitor group (SB-431542), and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…It can exert anticancer effects by inhibiting cell proliferation, inducing apoptosis, blocking the cell cycle, inducing autophagy, enhancing chemoradiation, inhibiting epithelial–mesenchymal transformation, inhibiting tumor metastasis, and inhibiting angiogenesis, such as in liver cancer, breast cancer, liver cancer, pancreatic cancer, and colorectal cancer [ 183 ]. Studies have shown that serine inhibits the growth of transplanted hepatocellular carcinoma (HCC) in mice and reduces the CD4 + CD25 + Foxp3 + proportion of Treg and the expression levels of Foxp3 and TGFβ mRNA, and enhanced the body’s antitumor immune response by inhibiting the TGF/SMAD signaling pathway [ 184 ]. Furthermore, it reduced the expression and activity of Akt and ER, and this inhibitory effect may contribute to inactivated PI3K/Akt and ER signaling pathways in human endometrial cancer cells [ 185 ].…”
Section: Natural Products In Preventing Tumor Drug Resistancementioning
confidence: 99%
“…It can exert anticancer effects by inhibiting cell proliferation, inducing apoptosis, blocking the cell cycle, inducing autophagy, enhancing chemoradiation, inhibiting epithelial–mesenchymal transformation, inhibiting tumor metastasis, and inhibiting angiogenesis, such as in liver cancer, breast cancer, liver cancer, pancreatic cancer, and colorectal cancer [ 183 ]. Studies have shown that serine inhibits the growth of transplanted hepatocellular carcinoma (HCC) in mice and reduces the CD4 + CD25 + Foxp3 + proportion of Treg and the expression levels of Foxp3 and TGFβ mRNA, and enhanced the body’s antitumor immune response by inhibiting the TGF/SMAD signaling pathway [ 184 ]. Furthermore, it reduced the expression and activity of Akt and ER, and this inhibitory effect may contribute to inactivated PI3K/Akt and ER signaling pathways in human endometrial cancer cells [ 185 ].…”
Section: Natural Products In Preventing Tumor Drug Resistancementioning
confidence: 99%
“…Tumor immune escape refers to the phenomenon in which tumor cells escape recognition and attack by the body’s immune system through a variety of mechanisms, so as to survive and proliferate in the body. It is reported that Solanine may enhance the antitumor immune response by downregulating the proportion of CD4+ CD25+ Treg and the expression of Foxp3 and TGFβ in tumor tissues ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Solanine is a steroidal alkaloid extracted from Solanum tuberosum Linn. Studies have found that solanine can enhance the anti-tumor immune response by down-regulating CD4 + CD25 + Tregs in tumor tissue and down-regulating the expression of Foxp3 and TGF-β ( Gao et al, 2020 ).…”
Section: Therapeutic Effect Of Bioactive Substances On Liver Cancermentioning
confidence: 99%